Implementasi Kebijakan Pengendalian Angka Kelahiran di Kabupaten Karawang - Nadila Rahmawati; Usep Dayat; Sopyan Resmana Adiarsa (Peneliti.net, 2022)
This paper is motivated by the phenomenon of the development of industrial estates, the rate of population growth and acculturation in the Karawang Regency area. The results of this study are Karawang as one of the largest industrial areas in Indonesia has given birth to the phenomenon of high levels of urbanization or population mobility both from outside the Karawang Regency area and from the Karawang village. This fact has implications for the rapid rate of population growth; crime rates and increasingly limited facilities and infrastructure for residents such as housing and other facilities. The Karawang Regency Government has issued policies to overcome these negative implications, among others, by initiating various breakthroughs, both persuasive and through various related policies. In the end, it is recommended to carry out population registration periodically by cutting holders, justification and counseling operations in Karawang Regency so that it can be known which permanent and non-permanent residents, especially in industrial areas and the importance of formulating special policies and policies. control of population administration in industry